Impact Analysis of a Business Model Adoption Based on Circular Economy for Coffee Bars in the City of Tijuana, Mexico - Sanchez, Cortez; Ricardo (Journal of Environmental Accounting and Management, 2026)
The increase in local consumption and the opening of formal business units called coffee bars in the city of Tijuana, Mexico, reveals significant business opportunities that could benefit, as stated by the Mexican Coffee Association (2017) [1], from the implementation of a business model based on the circular economy theory, with the aim of maximizing the positive impact in the region. These establishments, which represent one of the most dynamic commerce and gastronomy sectors, have not been sufficiently considered by current public policies or by the regulatory framework in terms of promoting sustainable development. In summary, there is a lack of greater impetus for activities such as recycling and the promotion of a culture of sustainability that has a positive impact on economic benefit. Using a quantitative approach and the application of adjustment measures supported by circular economy theory, primary information was obtained from the business units under study, which led to an analysis of the structural equation model (SEM), whose findings allow proposing a sustainable business model for coffee shops in the city of Tijuana, B.C. With this, the opportunity arises to offer a roadmap that details mechanisms and characteristics so that the business units involved adopt strategies aimed at maximizing their positive environmental impact and fostering a culture of cooperation. This initiative could also increase business opportunities for the local business community, thus contributing to increasing economic complexity and economically benefiting both the local community and the entire related value chain in the region.